Housing in the United Kingdom Whose Crisis? - Lund, Brian (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
"Another excellent text from Brian Lund, bringing us all up to date on the housing crisis (or should that be crises?) besetting the UK. Brian's grasp of the facts and figures on the housing system is unparalleled. This is a must-read for all those who want to understand how UK housing has reached the state it is in today." - Peter Somerville, Professor of Social Policy, University of Lincoln, UK In this book, Brian Lund builds on contemporary housing crisis narratives, which tend to focus on the growth of a younger 'generation rent,' to include the differential effects of class, age, gender, ethnicity and place, across the United Kingdom. Current differences reflect long-established cleavages in UK society, and help to explain why housing crises persist. Placing the UK crises in their global contexts, Lund provides a critical examination of proposed solutions according to their impacts on different pathways through the housing system. As the first detailedanalysis of the multifaceted origins, impact and potential solutions of the housing crisis, this book will be of vital interest to policy practitioners, professionals and academics across a wide range of areas, including housing studies, urban studies, geography, social policy, sociology, planning and politics.